2011
DOI: 10.1111/j.1475-1313.2011.00882.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors for pterygium and pinguecula in a South Indian population

Abstract: The prevalence of pterygium and pinguecula a South Indian population were 9.5% and 11.3% respectively. Rural residence were associated with presence of both pterygium and pinguecula. Higher lifetime UV exposure was associated with the presence of pterygia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
92
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(109 citation statements)
references
References 21 publications
13
92
4
Order By: Relevance
“…The present study has shown that the presence of the GSTM1-null genotype did not increase the possibility of developing pterygium in patients who smoke. These results are supported by those from a group of scientists from India (Asokan et al, 2012), who evaluated the effect of smoking in relation to pterygium. A further study conducted with Latin American patients living in the United States also found no significant difference regarding pterygium and smoking (West and Muñoz, 2009).…”
Section: Discussionsupporting
confidence: 75%
“…The present study has shown that the presence of the GSTM1-null genotype did not increase the possibility of developing pterygium in patients who smoke. These results are supported by those from a group of scientists from India (Asokan et al, 2012), who evaluated the effect of smoking in relation to pterygium. A further study conducted with Latin American patients living in the United States also found no significant difference regarding pterygium and smoking (West and Muñoz, 2009).…”
Section: Discussionsupporting
confidence: 75%
“…One of the theories is that the tear film abnormalities causes local drying of the cornea and conjunctiva which in turn predisposes to these new growths (Paton, 1975). The differential diagnosis of pterygium includes limbal masses which in order of their frequency, are pseudopterygium, papilloma, squamous cell conjunctival carcinoma, conjunctival melanoma, and pagetoid or sebaceous carcinoma (Char, 1987).There is a worldwide distribution of pterygium, but it is more common in warm, dry climates and after exposure to (both UV-A and UV-B) ultraviolet radiation (Detels et al, 1967;Asokan et al, 2012). Although the prevalence of the lesion increases with age, the highest incidence occurs between the ages of 20 and 49 years (Hilgers, 1960).…”
Section: Introductionmentioning
confidence: 99%
“…This is probably due to males forming majority (68.00%) of the study sample. Several studies have reported gender to be an independent predictor of pterygium, with males more likely to develop pterygium than females [15,17,20,24,29,[34][35][36][37]. The Tanjong Pagar survey reported males to be five times more likely to develop pterygium than females [38].…”
Section: Resultsmentioning
confidence: 99%
“…Several risk factors have been identified for development of pterygium. These include ultraviolet (UV) light exposure, exposure to irritants such as dust, smoke and wind, dry ocular surface and inflammation [15][16][17][18][19][20][21][22][23][24][25]. Ultraviolet (UV) light exposure is believed to be the single most important risk factor for development of pterygium [26].…”
Section: Introductionmentioning
confidence: 99%